Formula and preparation method of carbon fiber adsorption material
By adopting a blend system of polyacrylonitrile-based carbon fiber and activated carbon, combined with other fibers and adhesives, a carbon fiber adsorption material with strong comprehensive adsorption capacity is formed, which solves the problems of incomplete adsorption, limited scope and poor stability in the prior art, and achieves efficient adsorption and stable treatment of complex pollutants.
Patent Information
- Application Number
- CN202510129750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to meet the needs of efficient adsorption, broad-spectrum adsorption and strong stability in the electroplating industry and industrial wastewater treatment, especially when facing complex pollutants.
A blending system of polyacrylonitrile-based carbon fiber and activated carbon is used to combine diatomaceous earth, polyacrylammonium, methacrylate glue, polyvinyl alcohol fiber and needle wood pulp fiber to form a carbon fiber adsorption material with strong comprehensive adsorption capacity.
It has achieved efficient adsorption of small-molecular pollutants, tiny particulate impurities, organic pollutants, and bacterial pollutants, expanded the adsorption range, improved the adsorption stability and rate, and is suitable for electroplating industry and industrial wastewater treatment.
Smart Images

Figure CN119869478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adsorption materials, and in particular to a formula and a preparation method of a carbon fiber adsorption material. Background Art
[0002] For the electroplating industry, since the cost of the chemicals used in the electroplating process is relatively complicated, there will be some impurities in the workpiece to be plated, the electroplating equipment, and the air. In addition, some organic compounds will adhere to the surface of the workpiece to be plated, and some impurity-like heavy metal ions will be generated during the electroplating process. The electroplating brightener will decompose and produce impurities, which will be mixed into the electroplating chemicals. As a result, the chemicals in the electroplating tank contain more impurities and pollutants, including not only larger particles of impurities, but also microscopic particles of inorganic or organic pollutants, as well as bacteria and other pollutants, which affect the quality and efficiency of the electroplating process.
[0003] Similarly, with the development of industry, industrial wastewater generated by chemical, metallurgical, coking, light industry and other industries has shown the characteristics of increased discharge volume and complex composition. With the increase in urban population density, domestic wastewater has also shown the characteristics of increased discharge volume and complex composition. The wastewater contains more inorganic pollutants, organic pollutants, heavy metal ions, trichloroethylene, Escherichia coli and other pollutants. During the purification process, materials with strong adsorption capacity are needed for adsorption treatment.
[0004] In view of the above water treatment situations, activated carbon powder or a composite system with activated carbon powder as the main component is generally used for filtration and adsorption treatment. The good adsorption capacity of activated carbon for harmful pollutants, harmful gases, benzene pollutants, heavy metal ions and other pollutants can effectively adsorb most of the pollutants and make the treated water or solution clean.
[0005] However, since the adsorption of activated carbon generally relies on physical adsorption through the dense pore structure on its surface, and secondly uses chemical groups such as carboxyl and hydroxyl groups on its own surface to carry out chemical reaction adsorption, its adsorption mode is relatively simple and it is easy to reach adsorption saturation. After adsorption, pollutants are easily detached due to external interference, and the relative adsorption rate is low. The particle size range of pollutants that can be adsorbed is relatively limited, and there are relatively few adsorbable components. The adsorption capacity and efficiency for some organic matter are low. In the current complex pollutant environment, the adsorption capacity has gradually become difficult to meet application requirements.
[0006] Therefore, for more complex electroplating solution purification treatment and active industrial wastewater and domestic sewage treatment, the adsorption materials using the above-mentioned activated carbon powder system can no longer meet the application requirements of fast adsorption, wide range of adsorbable particle sizes, wide adsorbable components and strong adsorption stability.
[0007] Based on the above background, it is necessary to provide a formula and preparation method of a carbon fiber adsorption material with stronger comprehensive adsorption capacity. Summary of the invention
[0008] The present invention aims to solve the problems of the existing technology of the composite system of filtration and adsorption materials mainly for the electroplating industry, which has a relatively single filtration and adsorption target, a large limitation on adsorbable components, a low adsorption efficiency, and difficulty in meeting the needs of high-precision electroplating processing applications. First, a formula of a carbon fiber adsorption material is provided, and the formula components and weight proportions of the carbon fiber adsorption material are as follows: Polyacrylonitrile-based carbon fiber: 30 to 45 parts; Activated carbon: 30 to 40 parts; Silica bath soil: 5 to 10 parts; Polyacrylamide: 5 to 10 parts; Methacrylate glue: 30 to 50 parts; Polyvinyl alcohol fiber: 25 to 35 parts; Coniferous wood pulp fiber: 10 to 20 parts; Deionized water: 40 to 85 parts.
[0009] Furthermore, the compound system contains 5 to 10 parts of PAE wet strength agent.
[0010] Furthermore, the components and their weight proportions of the methacrylate adhesive are as follows: Methacrylic acid: 30 to 50 parts; Methyl methacrylate: 50 to 65 parts; Styrene: 20 to 40 parts; Butyl methacrylate: 25 to 40 parts; Octadecanyl methacrylate: 20 to 40 parts; Isopropyl alcohol: 35 parts to 35 parts; Ethanol: 35 parts to 35 parts; Benzoyl peroxide: 20 to 35 parts; Acrylic acid: 15 to 25 parts; Butyl acrylate: 30 to 60 parts; Deionized water: 50 to 85 parts.
[0011] Furthermore, the volume concentration of the methacrylate adhesive is 2% to 8% (preferably 5%).
[0012] Furthermore, the specific surface area of the polyacrylonitrile-based carbon fiber is 1000 m2 / g to 2000 m2 / g.
[0013] Furthermore, the activated carbon includes one or more of the following three types of activated carbon: Coconut shell activated carbon: 20 to 60 parts; Wood activated carbon: 20 to 50 parts; Coal-based activated carbon: 10 to 30 parts.
[0014] Further, The particle size of the coconut shell activated carbon is 200 mesh to 300 mesh; The particle size of the wood activated carbon is 150 mesh to 250 mesh; The particle size of the coal-based activated carbon is 200 mesh to 300 mesh.
[0015] The present invention also provides a method for preparing a carbon fiber adsorption material, wherein the preparation method uses the above-mentioned formula and is prepared according to the following process: S10: taking the methacrylate glue, adding the polyacrylamide to the methacrylate glue, and adding deionized water, stirring and uniformly mixing to form a first mixture; S20: adding the polyvinyl alcohol fiber and the coniferous wood pulp fiber into the first mixture, stirring and uniformly mixing, to form a second mixture; S30: adding the polyacrylonitrile-based carbon fiber, the activated carbon, and the silicate to the second mixture, and stirring the mixture to form the carbon fiber adsorption material.
[0016] Optionally, the step of adding the polyacrylonitrile-based carbon fiber, the activated carbon and the silicate to the second mixture is: S210: adding the polyacrylonitrile-based carbon fiber and the activated carbon to the diatomaceous earth, and adding deionized water, stirring and uniformly mixing to form a third mixture; S220: adding the third mixture into the second mixture, stirring and uniformly mixing, to form the carbon fiber adsorption material.
[0017] Optionally, the carbon fiber adsorption material is formed by adding the polyacrylonitrile-based carbon fiber, the activated carbon and the silicate into the second mixture, and adding the PAE wet strength agent, stirring and uniformly mixing to form the carbon fiber adsorption material.
[0018] The present invention adopts a blended system of polyacrylonitrile-based carbon fiber and activated carbon as the main adsorption component of the adsorption material, and utilizes the stronger adsorption force and faster adsorption speed of polyacrylonitrile-based carbon fiber on small molecular pollutants, tiny particle impurities, organic pollutants, and bacterial pollutants, and matches the adsorption capacity of activated carbon on impurities such as heavy metal ions, colored pollutants, sulfides, and nitrates, thereby forming a stronger adsorption system with a wider adsorption range, and with the help of the adsorption capacity of diatomaceous earth on larger molecular pollutants and good ion exchange performance, it can effectively adsorb some heavy metal cations, and has a good process of preventing the material system from forming a reverse escape after adsorbing impurities, and utilizing Ammonium polyacrylamide has good filter aid and flocculant properties, improves the chemical adsorption properties of polyacrylonitrile-based carbon fiber and activated carbon adsorption system, and flocculates in time after adsorption to form a gel to prevent the escape of adsorbed impurities and make it easy to clean up the impurities after adsorption. Methacrylate glue is used to form an adhesive slurry to give the adsorption material system a certain viscosity, which can be made into adsorption products of different shapes. Polyvinyl alcohol fiber is used to improve the dispersibility of the adsorption material system, enhance the overall tensile strength of the adsorption material, and improve the chemical resistance of the material. Coniferous wood pulp fiber is used to improve the strength and durability of the adsorption material system, so that it has better plasticity processing conditions.
[0019] The carbon fiber adsorption material provided by the present invention can adsorb organic substances including: hydrocarbons (benzene, toluene, xylene, trimethylbenzene, n-hexane, cyclohexane, etc.), halogenated hydrocarbons (methyl chloride, dichloromethane, chloroform, trichloroethylene, trichloroethane, methyl bromide, tetrachloride, etc.), aldehydes and ketones (acetone, cyclohexanone, formaldehyde, acetaldehyde, furfural, etc.), esters (ethyl acetate, butyl acetate, etc.), ethers (methyl ether, ethyl ether, methyl ethyl ether, etc.), alcohols (methanol, ethanol, isopropanol, butanol, etc.), and polymerization monomers (vinyl chloride, etc.).
[0020] It can be used for air purification and can effectively remove various harmful and smelly substances in the air, especially carcinogens and aromatic compounds (such as benzene and aldehydes), making the air clean and fresh.
[0021] It can be used for sewage treatment and is suitable for treating organic wastewater containing phenol, medicine, thiol and other organic wastewaters that are difficult to decompose.
[0022] It can be used for water treatment of food, beverage and medicine; decolorization and deodorization in sugar and wine industry, purification and sterilization of drinking water, and removal of residual chlorine in tap water.
[0023] It can be used for filtration and adsorption during the processing of some products in the electronics industry and new energy industry, and can achieve high-quality processing of products such as high-capacity capacitors, livestock battery electrodes, and conductive heating materials.
[0024] It can be used for protection, and can be used as raw materials for preparing rescue gloves, dressings, bandages and chemical protection screens, as well as raw materials for chemical protective clothing and bedding.
[0025] It can be used in water purifier products, which can not only purify water quality, but also have a good effect on the adsorption and removal of microorganisms in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0027] Figure 1 A method for preparing a carbon fiber adsorption material according to an embodiment of the present invention; Figure 2 The present invention provides another method for preparing a carbon fiber adsorption material according to an embodiment of the present invention.
[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0031] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0032] This embodiment first provides a formula of a carbon fiber adsorption material, the components and their weight parts are: First component: polyacrylonitrile-based carbon fiber: 30 parts to 45 parts, preferably 40 parts.
[0033] Optionally, the specific surface area is 1000 m2 / g to 2000 m2 / g, preferably 1300 m2 / g or 1600 m2 / g.
[0034] In this embodiment, short-cut polyacrylonitrile-based carbon fibers with a length of 2 mm to 7 mm are used, which have better adsorption performance during adsorption applications and are easy to process into products with film-like, sponge-like and other structural shapes.
[0035] Compared with activated carbon, polyacrylonitrile-based carbon fiber has a larger specific surface area and specific pore volume. The specific surface area is more than 100 times larger than that of activated carbon. The diameter of polyacrylonitrile-based carbon fiber is generally 10μm~20μm, and the surface and interior are composed of 0.8nm to 2.0nm micropores. Compared with granular or powdered activated carbon, it has more micropores and can directly adsorb the adsorbate. Therefore, polyacrylonitrile-based carbon fiber is more likely to produce capillary condensation, faster adsorption speed, and adsorption capacity is about 10 times or even higher than that of activated carbon particles; due to its special physical and chemical structure, it has a stronger and faster adsorption ability and interception effect on organic matter in the air, organic solvents in liquids, bacteria and suspended dust.
[0036] Second component: activated carbon: 30 to 40 parts, preferably 20 to 26 parts.
[0037] Optionally, the activated carbon includes one or more of the following three types of activated carbon: coconut shell activated carbon: 20 to 60 parts; wood activated carbon: 20 to 50 parts; coal-based activated carbon: 10 to 30 parts.
[0038] Since the present embodiment is aimed at the purification and adsorption of electroplating solutions in the electroplating industry during the processing process, as well as the treatment of industrial wastewater and domestic wastewater, it is required to have adsorption materials with different adsorption capacities, different adsorption speeds, and the ability to adsorb impurities of different particle sizes. Since polyacrylonitrile-based carbon fibers can mainly adsorb impurities with smaller particle sizes, bacteria, organic solvents and other impurities, some relatively large impurities (such as oxidized macromolecular brighteners in electroplating solutions, some heavy metal ions that react with organic solvents, etc.) are also required to have corresponding adsorption materials for effective adsorption.
[0039] Therefore, in the present embodiment, a portion of activated carbon is used as one of the key components to improve the comprehensive performance of the adsorption material, which plays a role in combination with the polyacrylonitrile-based carbon fiber.
[0040] Among them, optionally, coconut shell activated carbon can be used to directly adsorb heavy metal ions, oxidized macromolecular brightener molecules and other substances in the medicine or waste liquid, reducing or omitting the need to use potassium permanganate or hydrogen peroxide to carbonize the medicine or waste liquid, thereby saving energy and improving treatment efficiency; coconut shell activated carbon can be selected with a size of 200 to 300 mesh, preferably 250 mesh, an iodine value of 800 mg / g to 1200 mg / g, a specific surface area of 800 m2 / g to 1300 m2 / g, a methylene blue adsorption value of 220 mg / g to 300 mg / g, and a micropore diameter of 2nm to 30nm.
[0041] Optionally, the use of wood activated carbon can effectively adsorb relatively small small molecule impurities, has a good adsorption effect on impurities such as benzene impurities, chloroform, trichloroethylene, and has a good decolorization effect; the wood activated carbon can be selected from 150 mesh to 250 mesh, preferably 200 mesh, iodine value 800 mg / g to 1200 mg / g, specific surface area of 800 m2 / g to 1300 m2 / g, methylene blue adsorption value of 220 mg / g to 300 mg / g, micropore diameter of 2nm to 50nm, and caramel decolorization rate of 100% to 130%.
[0042] Optionally, the use of coal-based activated carbon can achieve effective desulfurization and denitrification effects, adsorb and remove sulfide and nitrate impurities in the medicine or waste liquid, and prevent sulfidation or nitrification of metal cations or other components that need to be retained; the coal-based activated carbon can be selected from 200 mesh to 300 mesh, preferably 250 mesh, with an iodine value of 800 mg / g to 1200 mg / g, a methylene blue adsorption value of 220 mg / g to 300 mg / g, a micropore diameter of 2nm to 50nm, and a caramel decolorization rate of 100% to 130%.
[0043] It should be noted that the present embodiment uses a mixture of the above three activated carbons to achieve comprehensive performance and a wide range of adsorption effects.
[0044] The third component: silicate: 5 to 10 parts, preferably 8 parts.
[0045] The main chemical components of diatomite are SiO 2 , containing a small amount of Al 2 O 3 , Fe 2 O 3 , CaO, MgO and other compounds, with a specific surface area of 100 m2 / g to 400 m2 / g. The micropore diameter of diatomaceous earth is widely distributed, ranging from 20 nm to 50 μm. This embodiment selects 20 nm to 5 μm.
[0046] Diatomaceous earth is used to further fill the gap in the adsorption range of polyacrylonitrile-based carbon fiber and activated carbon. The good distribution of mesopores and macropores of diatomaceous earth can effectively adsorb impurities with larger diameters. Its good electrostatic adsorption ability can effectively adsorb impurities such as suspended particles and heavy metal ions. Its good chemical adsorption ability can react chemically with organic matter and heavy metal ions through groups such as hydroxyl groups and carboxyl groups on the surface to form chemical adsorption. Its good ion exchange ability can be used to exchange with some negative ions in medicine or waste liquid to form adsorption of heavy metal ions or inorganic salts. Diatomaceous earth provides a wider range of adsorption capacity for the adsorption material compound system, and can use its own "photosynthesis-like" performance to effectively prevent and block the problem of reverse release of impurities after the polyacrylonitrile-based carbon fiber or activated carbon adsorption reaches saturation.
[0047] Fourth component: polyacrylamide: 5 to 10 parts, preferably 8 parts; In this embodiment, polyacrylamide is used as a flocculant. Due to the large number of functional groups on its molecules, it exhibits different degrees of charge in the solution. Through adsorption bridging and electrical neutralization, it is electrically neutralized with tiny particles in the water to form large-particle flocs, which promotes the aggregation of colloidal particles into large flocs and suspension separation. In the adsorption material compound system of this embodiment, it can promote and compensate for the adsorption action and adsorption effect of polyacrylonitrile-based carbon fiber, activated carbon and diatomaceous earth, so that the impurities and pollutants after adsorption can quickly form flocs and deposit at the bottom of the adsorption material. In terms of process, it can achieve the effect of quickly separating impurities and pollutants, and prevent reverse pollution after adsorption or mixed pollution caused by stirring of external solutions.
[0048] The fifth component: methacrylate glue: 30 to 50 parts, preferably 40 parts; In this embodiment, with its strong stability, good viscosity, and will not affect the comprehensive performance of the adsorption capacity of the polyacrylonitrile-based carbon fiber and the activated carbon adsorption system, it provides a structural basis for the dispersed components such as polyacrylonitrile-based carbon fiber, activated carbon and diatomaceous earth to be made into a specific geometric shape.
[0049] In this embodiment, the components and their weight proportions of the methacrylate adhesive are as follows: Methacrylic acid: 30 to 50 parts; Methyl methacrylate: 50 to 65 parts; Styrene: 20 to 40 parts; Butyl methacrylate: 25 to 40 parts; Octadecanyl methacrylate: 20 to 40 parts; Isopropyl alcohol: 35 parts to 35 parts; Ethanol: 35 parts to 35 parts; Benzoyl peroxide: 20 to 35 parts; Acrylic acid: 15 to 25 parts; Butyl acrylate: 30 to 60 parts; Deionized water: 50 to 85 parts.
[0050] The above can form a colloid with good viscosity, good high temperature resistance, durability, and chemical resistance, and can be further dried and processed later. Before a specific geometric structure is formed in the compound system of this embodiment, it has a storage time of 1 to 3 years and is not easy to naturally stick together.
[0051] In this embodiment, the volume concentration of the methacrylate glue is 2% to 8% (preferably 5%).
[0052] By using methyl methacrylate glue with a relatively low volume concentration, the composite system of this embodiment is processed during application to form a specific geometric shape structure, and then dried to evaporate a large amount of internal water, so that the composite system is transformed from a solution state to a solid state, and will not clog and affect the adsorption capacity of key adsorption components such as polyacrylonitrile-based carbon fiber, activated carbon and diatomaceous earth. In addition, it has strong stability during application and is not prone to deformation, rupture, or falling of the filter device with a specific geometric shape structure.
[0053] Sixth component: polyvinyl alcohol fiber: 25 to 35 parts, preferably 30 parts; By utilizing the high strength, high modulus, low elongation, wear resistance, good affinity with solvents, acid and alkali resistance and other good weather resistance properties of polyvinyl alcohol fibers, the strength and toughness of the specific geometric structure formed by the compound system of this embodiment are increased, and the plasticity and stability are improved. In addition, polyvinyl alcohol fibers have good dispersibility in the solution, which effectively improves the dispersion and uniform mixing capabilities of the components of the compound system.
[0054] In this embodiment, the polyvinyl alcohol fiber can be selected from polyvinyl alcohol fiber, water-soluble polyvinyl alcohol fiber, or a polyvinyl alcohol-based binder, or a mixture of two or more thereof.
[0055] Seventh component: softwood pulp fiber: 10 to 20 parts, preferably 16 parts; By utilizing the longer fiber length, relatively simple fiber components, and better flexibility of coniferous wood pulp fibers, the plasticity of the composite system of this embodiment to form a specific geometric structure can be improved, thereby increasing the traction force of each component of the system structure.
[0056] In the formula of the adsorption material of this embodiment, key adsorption components of polyacrylonitrile-based carbon fiber, activated carbon, silica clay and polyacrylamide are formed as adsorption components that mainly adsorb organic matter, heavy metal ions, impurity particles and other substances. The methyl methacrylate glue, polyvinyl alcohol fiber and coniferous wood pulp fiber components are formed to make the formula have strong stability and plasticity that can be processed into specific geometric shapes in the later stage. The formula system also has good properties such as non-toxicity, environmental protection, strong ingredient stability, strong high temperature resistance, strong chemical resistance, not easy to decompose itself, not easy to fall off, etc. It can be effectively used in the purification of chemical water in the electroplating industry, as well as the treatment of industrial wastewater and domestic wastewater.
[0057] In this embodiment, the compound system contains 5 to 10 parts of PAE wet strength agent, preferably 8 parts.
[0058] PAE wet strength agent is polyamide polyepichlorohydrin resin, with a content of 12.5%±0.5%, a pH value of 4-5, and a viscosity of 35mpa·s to 70mpa·s. PAE wet strength agent is added to this formula to take advantage of its strong adsorption effect on negatively charged fillers, slurries and fine fibers. Its good retention and filtration properties can improve the formula's anti-surface powder and dust performance.
[0059] See also Figure 1 , Figure 1 The invention relates to a method for preparing a carbon fiber adsorption material.
[0060] This embodiment also provides a method for preparing a carbon fiber adsorption material, which uses the above-mentioned formula and is prepared according to the following process: Step S10: Take methacrylate glue, add polyacrylamide to the methacrylate glue, and add an appropriate amount of deionized water, stir until uniformly mixed to form a first mixture; Step S20: Adding polyvinyl alcohol fiber and coniferous wood pulp fiber to the first mixture, and optionally adding an appropriate amount of deionized water, stirring until uniformly mixed to form a second mixture; Step S30: Add polyacrylonitrile-based carbon fiber, activated carbon and silicate to the second mixture, and optionally add a proper amount of deionized water, and stir until uniformly mixed to form a carbon fiber adsorption material.
[0061] In this embodiment, the volume concentration of the formed carbon fiber adsorption material is 5% to 15%, preferably 10%.
[0062] The above preparation method adopts a single cylinder direct mixing method, which has the characteristics of high preparation efficiency and simple preparation process, and can realize the effective preparation of carbon fiber adsorption materials; but at the same time it is difficult to achieve continuous production, and the proportion of component usage is difficult to control due to the residual components in the cylinder.
[0063] See also Figure 2 , Figure 2 The invention is another method for preparing carbon fiber adsorption material.
[0064] In this embodiment, polyacrylonitrile-based carbon fiber, activated carbon and silicate are added to the second mixture, as follows: Step S210: Adding polyacrylonitrile-based carbon fiber and activated carbon to diatomaceous earth, and adding an appropriate amount of deionized water, and stirring to form a third mixture; Step S220: The third mixture is added to the second mixture, and optionally, a proper amount of deionized water is added, and stirred to form a carbon fiber adsorption material.
[0065] The above preparation method adopts three cylinders for preparation, the first cylinder independently completes the mixing process of step S10, the second cylinder independently completes the mixing process of step S210, and the third cylinder completes the mixing process of step S220, forming a process in which the first cylinder mixes and prepares various auxiliary components, the second cylinder mixes and prepares key adsorption components, and the third cylinder mixes and prepares carbon fiber adsorption materials. On the one hand, the auxiliary components and the adsorption components are mixed and prepared in separate cylinders, which effectively forms continuous and independent processing of materials, prevents cross-contamination of materials with different functions during processing, especially prevents cross-contamination of components caused by the scattering of polyacrylonitrile-based carbon fibers and activated carbon, and improves the accuracy of the amount of each component. On the other hand, it can effectively form independent control, increase the equipment requirements of independent components according to processing requirements, and at the same time realize a continuous preparation process with more accurate amounts of each component.
[0066] In this embodiment, no matter which of the above two preparation methods is used, PAE wet strength agent can be added to the second mixture and stirred to form a carbon fiber adsorption material.
[0067] It is worth noting that after the carbon fiber adsorption material prepared in this embodiment is used to make a product with a specific geometric structure, before drying, the PAE wet strength agent solution (volume concentration of 2% to 8%, preferably 5%) can be evenly coated, sprayed or brushed onto the surface of the product with a specific geometric structure, which can also play a role in preventing surface powder and dust.
[0068] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A formula of a carbon fiber adsorption material, characterized in that: The formula components and weight proportions of the carbon fiber adsorption material are as follows: Polyacrylonitrile-based carbon fiber: 30 to 45 parts; Activated carbon: 30 to 40 parts; Silica bath soil: 5 to 10 parts; Polyacrylamide: 5 to 10 parts; Methacrylate glue: 30 to 50 parts; Polyvinyl alcohol fiber: 25 to 35 parts; Coniferous wood pulp fiber: 10 to 20 parts; Deionized water: 40 to 85 parts.
2. The formula of a carbon fiber adsorption material according to claim 1, characterized in that: The compound system contains 5 to 10 parts of PAE wet strength agent.
3. A formula of a carbon fiber adsorption material according to claim 1 or 2, characterized in that: The components and weight proportions of the methacrylate adhesive are as follows: Methacrylic acid: 30 to 50 parts; Methyl methacrylate: 50 to 65 parts; Styrene: 20 to 40 parts; Butyl methacrylate: 25 to 40 parts; Octadecanyl methacrylate: 20 to 40 parts; Isopropyl alcohol: 35 parts to 35 parts; Ethanol: 35 parts to 35 parts; Benzoyl peroxide: 20 to 35 parts; Acrylic acid: 15 to 25 parts; Butyl acrylate: 30 to 60 parts; Deionized water: 50 to 85 parts.
4. The formula of a carbon fiber adsorption material according to claim 3, characterized in that: The volume concentration of the methacrylate glue is 2% to 8%.
5. The formula of a carbon fiber adsorption material according to claim 1, characterized in that: The specific surface area of polyacrylonitrile-based carbon fiber is 1000 m2 / g to 2000 m2 / g.
6. The formula of a carbon fiber adsorption material according to claim 1 or 2, characterized in that: The activated carbon includes one or more of the following three types of activated carbon: Coconut shell activated carbon: 20 to 60 parts; Wood activated carbon: 20 to 50 parts; Coal-based activated carbon: 10 to 30 parts.
7. The formula of a carbon fiber adsorption material according to claim 7, characterized in that: The particle size of the coconut shell activated carbon is 200 mesh to 300 mesh; The particle size of the wood activated carbon is 150 mesh to 250 mesh; The particle size of the coal-based activated carbon is 200 mesh to 300 mesh.
8. A method for preparing a carbon fiber adsorption material, characterized in that: The preparation method uses the formulation according to any one of claims 1 to 7 and is prepared according to the following process: S10: taking the methacrylate glue, adding the polyacrylamide to the methacrylate glue, and adding deionized water, stirring and uniformly mixing to form a first mixture; S20: adding the polyvinyl alcohol fiber and the coniferous wood pulp fiber into the first mixture, stirring and uniformly mixing, to form a second mixture; S30: adding the polyacrylonitrile-based carbon fiber, the activated carbon, and the silicate into the second mixture, stirring and uniformly mixing, to form the carbon fiber adsorption material.
9. The method for preparing a carbon fiber adsorption material according to claim 8, characterized in that: The step of adding the polyacrylonitrile-based carbon fiber, the activated carbon and the silicate to the second mixture is as follows: S210: adding the polyacrylonitrile-based carbon fiber and the activated carbon to the diatomaceous earth, and adding deionized water, stirring and uniformly mixing to form a third mixture; S220: adding the third mixture into the second mixture, stirring and uniformly mixing, to form the carbon fiber adsorption material.
10. The method for preparing a carbon fiber adsorption material according to claim 8 or 9, characterized in that: The forming of the carbon fiber adsorption material is as follows: The polyacrylonitrile-based carbon fiber, the activated carbon, and the silicate are added to the second mixture, and the PAE wet strength agent is added, and the mixture is stirred and evenly mixed to form the carbon fiber adsorption material.